INFLUENCE OF COACHING STYLES UPON PLAYERS’ PERFORMANCE - Alamgir Khan Qureshi; Muhammad Zafar Iqbal Butt; Muhammad Jamil (The Sky)
Current study was initiated for the purpose to assess the influence of different coaching styles on athletic performance. Population of the study was comprised of Hockey players of Registered Hockey Clubs of District Bannu KP, Pakistan. 128 hockey players were taken as sample of the study by using available sampling technique. A self-made likert type was used for the collection of relevant data. The collected data were processed through statistical package for social science (SPSS, version 26).  Based on data analysis the researcher concluded that coaching styles have a significant influence upon field hockey player’s performance. In addition, the researcher also concluded that supportive coaching styles has more positive influence upon field hockey player’s performance